1997
DOI: 10.1021/la970212i
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of N-Vinyl-2-Pyrrolidone under Anodic Polarization:  Characterization of the Modified Electrode and Study of the Grafting Mechanism

Abstract: The application of single step or multiple anodic potential steps to highly concentrated solutions of N-vinyl-2-pyrrolidone leads to the formation of poly(N-vinyl-2-pyrrolidone) (or PVP) films on platinum electrodes. These films are insoluble in a good solvent of the commercial polymer. Multiple potential steps yield thicker films than a single potential step. Moreover, the PVP film thickness is maximum for a working potential amplitude of 1.7 V. Above this potential, the polymer film deteriorates by oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…158 Sequential electrodeposition of ethyl acrylate (EA) and acrylonitrile (AN) onto nickel has also been achieved. 159 It should also be noted that N-vinyl-2pyrrolidone, 150,[160][161][162] methacrylonitrile, 135 and 4-vinylpyridine 158 can also be polymerised by anodic oxidation on a Pt surface. The only restriction to cathodic electrografting is that the substituent should not be reduced before the vinyl group, for examples vinylic compounds with OH groups cannot be electrografted as the proton is reduced before the vinyl group.…”
Section: Reductive Electrografting 31 Vinylicsmentioning
confidence: 99%
“…158 Sequential electrodeposition of ethyl acrylate (EA) and acrylonitrile (AN) onto nickel has also been achieved. 159 It should also be noted that N-vinyl-2pyrrolidone, 150,[160][161][162] methacrylonitrile, 135 and 4-vinylpyridine 158 can also be polymerised by anodic oxidation on a Pt surface. The only restriction to cathodic electrografting is that the substituent should not be reduced before the vinyl group, for examples vinylic compounds with OH groups cannot be electrografted as the proton is reduced before the vinyl group.…”
Section: Reductive Electrografting 31 Vinylicsmentioning
confidence: 99%
“…Fourth, an in situ study with an electrochemical quartz crystal microbalance (EQCM) on the electrografting of MAN and Nvinylpyrrolidone (NVP) in anhydrous acetonitrile under cathodic and anodic conditions, respectively, clearly showed that for the latter monomer, which is known to afford only the grafted polymer because the dimer formed after desorption of the grafted radical cation is highly stable, [39] the equivalent resistance of the quartz crystal electrode remains almost constant during electrodeposition. At the same time, the eigenfrequency of the quartz exhibits large variations.…”
Section: Grafted Versus Nongrafted Films: Film Thicknessmentioning
confidence: 99%
“…Polyvinylpyrrolidone (PVP), a water‐soluble polymer with amphiphilic character, also possess outstanding features such as solubility, film and complex formation, adhesive and bonding power as toxicological harmlessness. This has led to an extensive investigation for varied prospective applications in the fields of cosmetics, pharmaceutical, medicine and industrial production …”
Section: Introductionmentioning
confidence: 99%